Ketentuan Pidana Dalam Perjanjian Fidusia Terkait Perlindungan Konsumen Perusaan Pembiyayaan Di Sumatera Selatan - Sanjaya, Eka Wahyu; Djatmiko, Sugeng; Khairi, Ilman (PT Elaborium Elevasi Indonesia, 2025)
It becomes clear from the examination of consumer protection offenses connected to fiduciary assurance agreements that an agreement, though a civil law document, might have a criminal component. Article 62 of Law Number 8 of 1999 concerning Consumer Protection, notably Article 18, about the provisions of standard clauses, contains information on the criminal implications of fiduciary guarantee agreements. Articles 35 and 36 of Law Number 42 of 1999 concerning Fiduciary Guarantees detail additional criminal issues. In light of this criminal component, the Consumer Dispute Settlement Agency (BPSK), an organization established under the Consumer Protection Law, is tasked with monitoring the incorporation of standard clauses and notifying the public prosecutor of any infractions of the law's provisions. Investigators typically connect it to the crimes of embezzlement and document forgery. The problem statement,